2018
DOI: 10.1111/tpj.13892
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the proteome of the problem weed blackgrass correlating with multiple‐herbicide resistance

Abstract: SummaryHerbicide resistance in grass weeds is now one of the greatest threats to sustainable cereal production in Northern Europe. Multiple‐herbicide resistance (MHR), a poorly understood multigenic and quantitative trait, is particularly problematic as it provides tolerance to most classes of chemistries currently used for post‐emergence weed control. Using a combination of transcriptomics and proteomics, the evolution of MHR in populations of the weed blackgrass (Alopecurus myosuroides) has been investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(89 citation statements)
references
References 39 publications
3
86
0
Order By: Relevance
“…This suggested that GSTs must possess alternative protective activities in NTSR that do not directly involve herbicide detoxification. However, it is known that the complex NTSR trait in different weed species is multi-genic (Duhoux et al 2017b;Keith et al 2017;Tétard-Jones et al, 2018), suggesting that a single GST cannot confer multiple resistance alone. In further investigating the roles of these proteins in NTSR, we now report the detailed characterization of the all detectable GSTs (the 'GSTome'), associated with herbicide resistance using a combination of transcriptomics, proteomics and functional expression of the respective recombinant enzymes.…”
Section: Blackgrass (Alopecurus Myosuroides)mentioning
confidence: 99%
See 3 more Smart Citations
“…This suggested that GSTs must possess alternative protective activities in NTSR that do not directly involve herbicide detoxification. However, it is known that the complex NTSR trait in different weed species is multi-genic (Duhoux et al 2017b;Keith et al 2017;Tétard-Jones et al, 2018), suggesting that a single GST cannot confer multiple resistance alone. In further investigating the roles of these proteins in NTSR, we now report the detailed characterization of the all detectable GSTs (the 'GSTome'), associated with herbicide resistance using a combination of transcriptomics, proteomics and functional expression of the respective recombinant enzymes.…”
Section: Blackgrass (Alopecurus Myosuroides)mentioning
confidence: 99%
“…As described above, from the growing body of transcriptome data, it is clear that GSTs from different classes are associated with NTSR in many weed species. Since it is known that the complex NTSR trait in different weed species is multi-genic (Duhoux et al 2017b;Tétard-Jones et al, 2018), it is clear that a single GST cannot confer multiple resistance alone. However, GSTs would be prima candidates for having functional roles in NTSR, given their close association in counteracting multiple types of biotic and abiotic stress in plants (Cummins et al 1999).…”
Section: Blackgrass (Alopecurus Myosuroides)mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, grass weeds can develop nontarget site resistance (NTSR) to multiple herbicide chemistries through increased detoxification. This mechanism also is termed enhanced metabolic resistance (EMR) and has been recorded in many grass weeds . EMR is associated with the enhanced expression of herbicide detoxifying enzymes, notably cytochrome P450 monooxygenases (CYP450s) and glutathione transferases (GSTs) .…”
Section: Introductionmentioning
confidence: 99%